Developing skills learning in obstetric nursing: approaches between theory and practice - Maria de Fátima Gomes Lima; Alice Maria Correia Pequeno; Dafne Paiva Rodrigues; Cleide Carneiro; Ana Patrícia Pereira Morais; Francisca Diana da Silva Negreiros
ABSTRACT Objective: To analyze the development of professional skills in an obstetric nursing graduate course. Method: Qualitative research, applying semi-structured interviews with 11 students in the obstetric nursing specialization at the State University of Ceará. Data was submitted to thematic review. Results: According to the subjects, the course offers the development of skills to strengthen and expand the range of activities in obstetric nursing. Despite relying on previous knowledge and experience acquired by the students, there is a gap between the content taught and internship practice, presented as challenges and difficulties faced by the students. The findings suggest a need for curricular revision, incorporating active teaching-learning methodologies, to overcome the disjunction between theory and practice. Final considerations: Students are part of a corpus that is potentially implicated in the construction and transformation of thoughts and values set forth by educational and health institutions, and it is necessary to make changes in political and social organizations, with a focus on providing comprehensive and egalitarian care to the population.